2018
DOI: 10.1038/s41598-018-31600-5
|View full text |Cite
|
Sign up to set email alerts
|

Time-advanced occurrence of moderate-size earthquakes in a stable intraplate region after a megathrust earthquake and their seismic properties

Abstract: The distance-dependent coseismic and postseismic displacements produced by the 2011 MW9.0 Tohoku-Oki megathrust earthquake caused medium weakening and stress perturbation in the crust around the Korean Peninsula, increasing the seismicity with successive ML5-level earthquakes at the outskirts of high seismicity regions. The average ML5-level occurrence rate prior to the megathrust earthquake was 0.15 yr−1 (0.05–0.35 yr−1 at a 95% confidence level), and the rate has increased to 0.71 yr−1 (0.23–1.67 yr−1 at a 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 48 publications
(79 reference statements)
5
33
0
1
Order By: Relevance
“…The pdf of the focal depth for the Pohang earthquake is 5.0 ± 0.8 (2σ) km, ranging from~4 to 6 km ( Figure 3c). The previous estimates of 4.27 km (KGC, 2019) and 6.2 km (Hong et al, 2018) are within our determined range, which corresponds to the depth range of granodiorite basement (Lee et al, 2015).…”
Section: Pohang Earthquake Locationsupporting
confidence: 89%
See 2 more Smart Citations
“…The pdf of the focal depth for the Pohang earthquake is 5.0 ± 0.8 (2σ) km, ranging from~4 to 6 km ( Figure 3c). The previous estimates of 4.27 km (KGC, 2019) and 6.2 km (Hong et al, 2018) are within our determined range, which corresponds to the depth range of granodiorite basement (Lee et al, 2015).…”
Section: Pohang Earthquake Locationsupporting
confidence: 89%
“…The direction of the maximum horizontal principal stress (S Hmax ) is indicated by black arrows (Soh et al, 2018). The red and blue “X” symbols indicate the locations of the Pohang earthquake according to Hong et al (2018) and Woo et al (2019), respectively. (b) Epicentral pdf s of the Pohang earthquake and aftershocks.…”
Section: Poroelastic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…This substantial discrepancy highlights that observed larger magnitude earthquakes than expected should involve additional physical mechanisms enhancing accumulation and subsequent release of elastic energy. Previous studies of basin-scale Coulomb stress modeling indicated that successive earthquakes driven by tectonics could attribute to the stored strain energy along nearby faults (e.g., stress transfer and subsequent accumulation due to 2016 M w 5.5 Gyeongju earthquake 25,38 ). These studies suggest that even a slight increase in static stress may enhance the potential of earthquake nucleation along critically stressed faults located in the area under subsurface energy activities.…”
Section: Mitigation Of Seismic Hazards On Basement Faultsmentioning
confidence: 99%
“…The orientation of the most compressional stress axis changed from near N-S to ENE-WSW due to the change in the tectonic regime (Soh et al, 2018). Grigoli et al (2018) and Kim et al (2018) suggested the possibility that the 2017 Pohang earthquake was induced by the activities of an EGS located near (<1 km to the east) the epicenter (Figure 2), although some controversy remains (Hong et al, 2018). Several researchers suggested that the Pohang earthquake was triggered by accumulated seismicity related to an unknown unstable fault (Ellsworth et al, 2019;Geological Society of Korea, 2019;Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%